1991
DOI: 10.1002/jmor.1052080103
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycle of the chromaffin cells of Triturus cristatus

Abstract: Morphology of the chromaffin cells of Triturus cristatus during a complete annual cycle has been investigated. General ultrastructural characteristics are similar for all chromaffin cells, including numerous small mitochondria, well-developed Golgi apparatus and rough endoplasmic reticulum with short cisternae. The primary difference among cells is the type of the chromaffin granules they posses. These are of two kinds: adrenalin (A) and noradrenalin granules (NA). Both types are simultaneously present in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…2A) and July (Fig. 2B) have the general ultrastructural features previously described (Laforgia and Capaldo, 1991): a large nucleus with some heterochromatin close to the nuclear membrane, an endoplasmic reticulum made up of vesicles and short cisternae forming smooth (SER) or rough (RER) endoplasmic reticulum, numerous rounded or elongated mitochondria, and a well-developed Golgi apparatus. Noradrenalin granules are of variable shape and have a very electron-dense core, sometimes not separated from the limiting membrane.…”
Section: Transmission Electron Microscopymentioning
confidence: 90%
See 2 more Smart Citations
“…2A) and July (Fig. 2B) have the general ultrastructural features previously described (Laforgia and Capaldo, 1991): a large nucleus with some heterochromatin close to the nuclear membrane, an endoplasmic reticulum made up of vesicles and short cisternae forming smooth (SER) or rough (RER) endoplasmic reticulum, numerous rounded or elongated mitochondria, and a well-developed Golgi apparatus. Noradrenalin granules are of variable shape and have a very electron-dense core, sometimes not separated from the limiting membrane.…”
Section: Transmission Electron Microscopymentioning
confidence: 90%
“…Triturus carnifex has a single type of chromaffin cell, having an annual cycle with seasonal variations in the noradrenaline/adrenaline granule ratio within the cells. In the periods of the year characterized by extreme temperatures (winter or summer), there is a strong prevalence of NA granules; in the milder periods (autumn or spring), A and NA granules are present in the cells in almost equal quantities (Laforgia and Capaldo, 1991). The chromaffin cells in March ( Fig.…”
Section: Transmission Electron Microscopymentioning
confidence: 98%
See 1 more Smart Citation
“…The other classes of vertebrates behave differently: in amphibians PNMT is independent of the level of corticosteroids (Dupont et al, 1911;Laforgia & Capaldo, 1991), while in reptiles it is under the control of steroids secreted by the adrenal cortex (Laforgia & Varano, 1978b;Laforgia et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study (unpubl. data), we showed that in vivo acetylcholine (Ach) administration directly influenced the chromaffin cells, eliciting noradrenaline or adrenaline secretion, according to the period in the chromaffin cell functional cycle (Laforgia and Capaldo, 1991), and indirectly influenced the steroidogenic cells via the chromaffin cells. We suggested that Ach-induced noradrenaline secretion enhanced, whereas Ach-induced adrenaline secretion inhibited aldosterone release from steroidogenic cells.…”
mentioning
confidence: 96%